PERENCANAAN KONSEP KAWASAN WISATA KAMPUNG IKAN HIAS KELURAHAN SLIPI KECAMATAN KEMBANGAN KOTA ADMINISTRASI JAKARTA BARAT DKI JAKARTA - Pradini, Purnama Sakhrial; Adrianus Firmando Sihotang; Guntur Putra Pratama (Universitas Pelita Bangsa, 2021)
The Slipi ornamental fish cultivator area has been recognized for its quality and in accordance with the 2017-2022 DKI Jakarta RPJMD, the Slipi Area becomes an Area of Ornamental Fish Promotion and Marketing Centers (SPPIH) which prioritizes the development of the area. For this reason, a priority area arrangement for ornamental fish centers in Slipi, West Jakarta is needed which can produce regional planning concepts and programs that can improve ornamental fish promotion centers and improve the economy of the people in the area. slipi area design components, which include the following criteria: land use structure, intensity of land use, building structure, circulation systems and connecting lines, open space systems and green systems, environmental quality systems, environmental infrastructure and utility systems, building and environmental preservation. The direction for the development of slipi ornamental fish tourism is derived from the 7 elements of development of tourism development, the arrangement of the area on 7 indicators of sapta charm with 4 indicators of sapta charm that need to be resolved problems that occur in the field which are considered still bad.